2020
DOI: 10.1111/famp.12524
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐lagged Models of Marital Relationships and Intergenerational Conflicts during Transition to Parenthood: Effect of Patrilineal Coresidence

Abstract: The transition to parenthood is one of the most stressful intra-and interpersonal adjustment periods for new parents. Bidirectional associations among intergenerational relationships during the transition to parenthood have received limited attention, and the complexity of reciprocal relationships varies in accordance with living arrangements. The objectives of this study were to explore (1) the bidirectional associations between marital relationships and conflicts with in-laws during the transition to parenth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The transition to parenthood is an intense life event in which mothers and fathers experience new individual and family challenges, such as changes in roles, new family demands, chronic fatigue, financial pressures and conflicts between work and family life (Figueiredo et al, 2018 ), requiring the development of new skills and resources to face these changes (Rowe et al, 2013 ). The experiences of this adaptation process, when the dyadic marital relationship becomes a triadic or multiple relationships (Lau et al, 2020 ), impact individual well‐being, the conjugal relationship and the parent's ability to support their child during their early years (Young et al, 2019 ). Therefore, facilitating a positive transition is a topic of interest for researchers and health providers alike.…”
Section: Discussionmentioning
confidence: 99%
“…The transition to parenthood is an intense life event in which mothers and fathers experience new individual and family challenges, such as changes in roles, new family demands, chronic fatigue, financial pressures and conflicts between work and family life (Figueiredo et al, 2018 ), requiring the development of new skills and resources to face these changes (Rowe et al, 2013 ). The experiences of this adaptation process, when the dyadic marital relationship becomes a triadic or multiple relationships (Lau et al, 2020 ), impact individual well‐being, the conjugal relationship and the parent's ability to support their child during their early years (Young et al, 2019 ). Therefore, facilitating a positive transition is a topic of interest for researchers and health providers alike.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, maternal concerns further increase marital conflicts. 53 The study showed that pregnancy concern does not affect maternal competency. However, since the present study measured maternal competence prospectively 6 weeks after delivery, and in this study, pregnancy-specific concerns were examined, so the trend of time and initiation of the maternal transition process may reduce the impact of pregnancy-related problems and concerns on maternal competency.…”
Section: Discussionmentioning
confidence: 89%
“…As the initial transition to motherhood begins with pregnancy, there are concerns such as accepting new social roles, restrictions on freedom, and spending more time, energy, and budget, the quality of marital relationships affect these concerns during pregnancy. As a result, maternal concerns further increase marital conflicts 53 …”
Section: Discussionmentioning
confidence: 99%
“…Men may thus be reluctant to express their support needs or seek help amid concerns that to do so would detract from their partner's needs (Darwin et al, 2017). New fathers often do not have information about these psychological changes, and they require role models or instructions to prepare for adapting with TTP stage, especially about a relationship with a partner (Lau et al, 2020). Also, they need antenatal education/support programs (Trimarchi and Van Bavel, 2017).…”
Section: Resultsmentioning
confidence: 99%